Profil Perpustakaan Sekolah Sebagai Sumber Belajar Siswa di UPTD SD Negeri Kamal 1 - Winarsih, Tia; Puspitasari, Aditya Dyah (Yayasan Arrahman Nahdlatul Wathan, 2024)
The aim of this research is to analyze the condition of the library as a learning resource at UPTD SD Negeri Kamal 1. This research uses a descriptive qualitative method. The subjects of this research were the principal, librarian, teachers and students at UPTD SD Negeri Kamal 1. Samples were taken using a simple random sampling technique. The research sample consisted of 8 people, namely the principal, library guard, 2 teachers in grades 1 and 4, 4 students in grades 1, 2, 4, 5. The data collection techniques for this research are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions and verification. The results of this research show that: 1) the condition of the library at UPTD SD Negeri Kamal 1 is quite good, equipped with facilities and infrastructure such as a library room, strategically located, there are tables, chairs, books, etc; 2) the obstacles faced in utilizing the library as a learning resource, namely the book collection is not yet up to date, there are no permanent library staff, lack of library facilities; 3) efforts made by the school, namely empowering existing books, collaborating with other parties, and frequently holding mobile libraries.